The Buffering Role of Food Security in the Relationship between Food Price Volatility and Farmer Poverty - Asri Ambariah; Andi Din Mahsyar Magribi Usdar; Frederik Katupu; Bernadetha Lista; Patrick Antonio; Dalila Aurelia (Journal of Economics Business Industry, 2025)
This study examines the relationship between food price volatility, food security, and farmer poverty in six provinces of Java, Sumatra, and Sulawesi, Indonesia, over the period 2015-2023. Using a balanced panel dataset compiled from the Central Bureau of Statistics (BPS), the Food Security and Vulnerability Atlas (FSVA), and Bank Indonesia consumer price data, this study employs a two-way fixed-effects panel regression model augmented with an interaction term to capture the moderating role of food security on the poverty-volatility nexus. The results indicate that food price volatility exerts a statistically significant positive effect on farmer poverty rates (b = 0.389, p < 0.01), while food security exhibits a significant negative effect (b = -0.297, p < 0.01). The interaction term between food security and food price volatility is negative and significant (b = -0.081, p < 0.05), confirming that higher food security attenuates the adverse poverty effects of price volatility. These findings contribute to the literature on agricultural poverty traps by providing province-level evidence from a major developing economy and by quantifying the buffering capacity of food security systems. Policy implications point toward the urgency of strengthening national food reserves, improving market integration, and expanding social protection for smallholder farmers.